Analysis of the Application of Murabahah Contracts in Financing at the Rantau Prapat Branch of Sharia Bank - Manswab Mahsen Abdulrahman; Damia Hadifa; Suci Salsabila Lubis; Sultan Rayhan Adinata; Lidya Nailah Winanda (ISNU Sumatera Utara, 2025)
Murabahah contract is a financing contract where the bank as the seller states the acquisition price of the goods and takes a profit margin agreed upon with the customer. The problem formulation in this study includes (1) How is the regulation of financing implementation using the murabahah contract from an Islamic legal perspective at the Rantau Prapat branch of Bank Syariah Indonesia. (2) How is the implementation of murabahah at the bank in accordance with sharia principles? (3) How are the solutions to internal and external obstacles in the implementation of murabahah financing? The results of the study indicate that the regulation of the implementation of the murabahah contract in the Indonesian sharia sector follows the provisions of the fatwa of the National Sharia Council of the Indonesian Ulema Council Number DSN-MUI NO.04/DSN-MUI/IV/2000. Murabahah financing is used to finance customer business needs. Such as working capital, investment, people's business credit (KUR). As well as financing for the medium and main categories. Obstacles faced include late payments from customers and submission of false or invalid documents. The solutions implemented include a more precise evaluation of the eligibility of prospective customers and increased education regarding payment obligations.